KorSA from the Streptomyces Integrative Element pSAM2 Is a Central Transcriptional Repressor: Target Genes and Binding Sites - Sezonov, Guennadi (American Society for Microbiology, 2000)
pSAM2, a 10.9-kb mobile integrative genetic element from Streptomyces ambofaciens, possesses, as do a majority of Streptomyces conjugative plasmids, a kil-kor system associated with its transfer. The kor function of pSAM2 was attributed to the korSA gene, but its direct role remained unclear. The present study was focused on the determination of the KorSA targets. It was shown that KorSA acts as a transcriptional repressor by binding to a conserved 17-nucleotide sequence found upstream of only two genes: its own gene, korSA, and pra, a gene positively controlling pSAM2 replication, integration, and excision. A unique feature of KorSA, compared to Kor proteins from other Streptomyces conjugative plasmids, is that it does not directly regulate pSAM2 transfer. KorSA does not bind to the pSAM2 genes coding for transfer and intramycelial spreading. Through the repression of pra, KorSA is able to negatively regulate pSAM2 functions activated by Pra and, consequently, to maintain pSAM2 integrated in the chromosome.